A study about WebQuest : the importance of the process in group work - Carneiro, Anabela Gonçalves (2011)
This paper reports the findings of a quasi-experimental study conducted with two classes in their 2nd year of vocational education, which aimed at understanding the importance of the process in solving the WebQuest task and its implications in learning. This research implied the design and application of two long term WebQuests, using the English Language, entitled “Looking for a job in a hotel”. We observed that students who had the complete WebQuest were quicker to solve the activities, because they were guided in the roles that each element should perform. No statistical differences were obtained. The WebQuest enhanced students’ constructive role in the understanding of concepts related to the thematic. Students valued the work developed; they accomplished the activity successfully and considered the WebQuest an enriching experience.